Developing a model for life skills training through the enhancement of academic, personal, social, and career competencies for middle school students - Hafina, Anne; Rusmana, Nandang; Hamzah, Rifqy Muhammad; Irawan, Tb Moh Irma Ari; Mulyati, Srie (Journal of Education and e-Learning Research, 2024)
The objective of this research is to develop a model for life skills training through the strengthening of academic, personal, social, and career competencies for middle school students. We designed this model to equip students with the necessary skills to navigate the complexities of life’s challenges. Design-Based Research (DBR) serves as a research methodology, encompassing four stages: identification and analysis of practical problems, solution design, iterative testing cycles and solution refinement, reflection, and producing the final design. Validation testing of the model was conducted with four experts, including one developmental guidance and counseling specialist, one developmental psychologist, one adolescent psychologist, one curriculum and learning specialist, and eight guidance and counseling teachers or practitioners. The results of expert and practitioner validation indicate that the life skills training model is worthy of further experimentation to develop student’s life skills. Recommendations for future research emphasize the importance of developing new skills or competencies for the younger generation and educators to address the challenges and dynamics of the digital era. Globalization and societal shifts toward digitally automated services underscore the need for teacher preparation in imparting life skills that not only adhere to conventional norms but also integrate technological skills into student education.